Normoprolactinemic galactorrhea in a depressed adolescent: A case report. - Gibaja-Reyes, Diasania (2021)
Childhood/adolescence depressive disorder is a well-known clinical diagnosis recognized to cause structural and functional neuroendocrine impairment. Some of the risk factors are depressive symptoms in parents, dysfunctional family, chronic stress, physical, sexual or psychological child abuse. These disorders are associated with memory, language, emotional and hormonal dysregulations. During childhood, depressive symptoms tend to coexist with somatic symptoms due to the patients’ difficulties to express their emotions, reasons for which  these symptoms could be reason for seeking medical attention. The case of an adolescent with depressive disorder associated to normoprolactinemic galactorrhea is presented. Galactorrhea could be associated with hyperprolactinemia, but it could also be linked to chronic stress events and normoprolactinemia.